KADAR ASAM URAT METODE ENZIMATIK PADA SAMPEL SERUM DAN SAMPEL PLASMA EDTA (Studi di Puskesmas Tambakrejo Jombang) - Sri Sayekti (Universitas Harapan Bangsa Purwokerto, 2021)
Uric acid is the end product of purine metabolism. Purines are amine compounds that are part of the protein that make up the body. Uric acid is distributed to blood plasma, synovial fluid, liver and several other organs, then excreted by the kidneys in urine. Examination of uric acid levels is usually used serum and plasma EDTA samples. This study aims to determine the differences in uric acid levels with the enzymatic method in serum and plasma EDTA samples. This research uses analytic observation type with cross sectional approach. The population was all residents who participated in the counseling activities on the dangers of smoking, amounting to 33 people, a sample of 15 people taken by purposive sampling aged> 40 years. The data were processed using editing, coding, tabulating and analyzed using the independent T-test statistical test at an error level of 5%. The results showed that the serum sample had an average uric acid level of 6.76 mg / dl while the uric acid level of the EDTA plasma sample had an average of 6.79 mg / dl. The independent T-test was tolerated p = 0.729, p>α , H0 is rejected. The study concluded that there was no significant difference between the results of examining uric acid levels using serum samples and EDTA plasma samples.